0822 DOES SLEEP QUALITY DURING PREGNANCY INFLUENCE INITIATION AND CONTINUATION OF BREASTFEEDING?. (28th April 2017) - Gordon, LK; Mason, K; Quattrucci, JA; Boni, GM; Carr, SN; Sharkey, KM
Abstract: Introduction: Pregnant and postpartum women experience significant sleep disruption, but the role that perinatal sleep disturbance plays in breastfeeding is not well understood. This analysis examined whether differences in sleep quality during pregnancy predicted initiation and continuation of breastfeeding and the use of formula. We hypothesized that women with higher sleep efficiencies during pregnancy would be more likely to initiate and continue breastfeeding. Methods: We studied 48 women (mean age 28.2 ± 4.9 years) with a past history of major depression (n=43) or bipolar disorder (n=5) at 33 weeks gestation and postpartum weeks 2, 6, and 16. Sleep onset, sleep offset, and total sleep time (TST) were estimated with wrist actigraphy averaged over each week. Time in bed was defined as the duration between sleep onset and sleep offset, and sleep efficiency was calculated as TST ÷ Time in Bed x 100. We divided the sample into two groups: "lower sleep efficiency" (LSE) and "higher sleep efficiency" (HSE) based on a median split (cutoff was sleep efficiency = 84.9%). Breastfeeding status was obtained through daily diaries and structured interviews performed at the postpartum time points, and we classified new mothers as No-BF, Mixed-BF (breastfeeding with formula supplementation), and Exclusive-BF. Results: The percentages of women who did any breastfeeding were: Week 2=72.3%, Week 6=62.5%, Week 16= 50%. The LSE group was less likely than the HSE group to initiate breastfeeding (percent No-BF in LSE=45.8% vs. percent No-BF in HSE=16.7% Chi Square (df=1) = 4.752, p=.029). 62.5% of the Exclusive-BF group and 52% of the Mixed-BF groups were in the HSE group, compared to only 14% of the No-BF group (Chi Square (df=2) = 4.611, p=.10). Conclusion: In our sample of women a history of depression or bipolar disorder, preserved sleep efficiency during pregnancy was associated with initiation and continuation of breastfeeding. Breastfeeding is an important aspect of maternal and infant physical and mental health. Future work should examine how sleep impacts this complex behavior and whether interventions to improve sleep during pregnancy can increase breastfeeding. Support (If Any): MH086689 (KMS).